2013
DOI: 10.1681/asn.2013010033
|View full text |Cite
|
Sign up to set email alerts
|

Facility Size, Race and Ethnicity, and Mortality for In-Center Hemodialysis

Abstract: The association between dialysis facility size and mortality for patients undergoing hemodialysis remains largely unclear, and whether the relationship differs by race and ethnicity or among high-risk subgroups is not known. Using data from the USRDS, we analyzed mortality rates in 385,074 incident patients ages$18 years who received in-center hemodialysis at 4633 dialysis facilities between 2003 and 2009. Facilities were categorized by the number of hemodialysis stations (1-5, 6-10, 11-15, 16-20, 21-25, 26-30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…A review reported that the annual crude death rate was in the range of 9.0%–10.2% for dialysis populations in Japan [2]. Yan et al [3] followed up 385,074 HD patients and reported that the one-year mortality was 19.8% and the five-year mortality was 43.0%. The high mortality of HD may be due to the plenty of vascular complications, such as vascular calcification [4] and atherosclerosis [5].…”
Section: Introductionmentioning
confidence: 99%
“…A review reported that the annual crude death rate was in the range of 9.0%–10.2% for dialysis populations in Japan [2]. Yan et al [3] followed up 385,074 HD patients and reported that the one-year mortality was 19.8% and the five-year mortality was 43.0%. The high mortality of HD may be due to the plenty of vascular complications, such as vascular calcification [4] and atherosclerosis [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that patients in smaller HD facilities have either more comorbidities or worse pre‐ESRD care . In our cohort, patients treated in smaller HD units displayed more unfavourable prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…This threshold size is much higher than that reported by Yan et al Notably, the size of HD facilities in Taiwan is larger than that in the United States. In the study of Yan et al , only 7.8% of patients received HD in facilities with ≥31 stations . In the present study, 13.9% and 3.9% of patients in freestanding HD units were treated in facilities with 31–45 and ≥ 45 stations, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations